Coefficient Estimates and Other Properties for a Class of Spirallike Functions Associated with a Differential Operator. (5th June 2013) - Orhan, Halit; Răducanu, Dorina; Çağlar, Murat; Bayram, Mustafa
Abstract : For 0 ≤ η < 1, 0 ≤ λ < 1, − π / 2 < γ < π / 2, 0 ≤ β ≤ α, and m ∈ ℕ ∪ { 0 }, a new class S α, β m ( η, γ, λ ) of analytic functions defined by means of the differential operator D α, β m is introduced. Our main object is to provide sharp upper bounds for Fekete-Szegö problem in S α, β m ( η, γ, λ ) . We also find sufficient conditions for a function to be in this class. Some interesting consequences of our results are pointed out.